Pengaruh independensi, kompetensi, moral reasoning, dan skeptisisme profesional auditor pemerintah terhadap kualitas audit laporan keuangan pemerintah daerah - Katuruni, Innas Susantira (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
This study aims to analyze the effect of independence, competence, moral reasoning, and professional skepticism of government auditors on the audit quality of local government financial statements. The attitude of independence, competence, moral reasoning, and professional skepticism of auditors are some of the attitudes that government auditors should have in their duties to audit financial statements so as to produce audit quality in accordance with what is desired. These attitudes can be explained as the attitude of conducting the audit in accordance with the specified stages, certainty in knowing the type and amount of evidence to be collected, attitudes based on moral awareness that influence ethical decision making, and critical thinking in questioning and evaluating audit evidence. While audit quality is the ability of the auditor to find errors during the audit process and report them to interested parties. In this study using objects, including government auditors who are in the Inspectorate of the Special Region of Yogyakarta and government auditors who are in the Department of Revenue, Financial Management and Assets of the Special Region of Yogyakarta. The inspectors designated as objects consist of the Gunungkidul Regency Inspectorate, Kulonprogo Regency Inspectorate, Bantul Regency Inspectorate, Sleman Regency Inspectorate, Yogyakarta City Inspectorate, and Yogyakarta Special Region Province Inspectorate. The data obtained in this study was carried out using the primary data collection method obtained from research techniques in the form of a questionnaire.